Influência dos antagonistas LINS01005 e LINS01007 nos receptores de histamina H3/H4 em modelo de asma murino - Lima, Leandro Jose Sousa [UNIFESP] (2019)
Histamine is a biogenic amine that originates from the decarboxylation of the amino acid histidine. It is stored in intracellular granules and is rapidly secreted as soon as cellular activation occurs or is synthesized in response to an inflammatory or allergic stimulus through binding between its specific receptors in the target cell. It was initially used as inducer of smooth muscle contraction, but today with the knowledge of receptors like H3R and H4R. The H4R receptor has been the most studied in recent years in models of pulmonary inflammation, and has been shown to be a promising drug target for the treatment of respiratory diseases. Inhibition of H4 receptors is an effective means of decreasing some of the biological effects of asthma. In view of the therapeutic arsenal still far from ideal for the treatment of chronic inflammatory diseases, the objective of this project is to synthesize and evaluate the activity of dihydrobenzofurylpiperazine compounds in search of a probable antiasthmatic activity. The compounds of the LINS01 series were designed as potential H4R ligands. Allergic pulmonary response was studied in these animals at 10 weeks of age. The characterization of the inflammatory response was performed by analysis of the cellular infiltrate in the bronchoalveolar lavage, where we verified a smaller cellular infiltrate in the lungs of the mice treated with the H4R antagonists LINS01005 and LINS01007. Protein expression of COX-2, 5-LO, NF-κB and STAT3 were performed by western blotting, whereas the cytokines were quantified by multiplex assay. Mice sensitized and challenged with OVA, increased the cellular infiltrate and the protein expression of COX-2, 5-LO, NF-κB and STAT3, and protein expression of COX-2, 5-LO, NF-κB and STAT3, in addition to increased production of cytokines IL-4, IL-5, IL-13, IL-1α, TNF-α, IFN-γ and RANTES. Treatment with LINS01007 at a dose of 3mg / kg attenuated all effects of asthma induced in this model. Our results showed a better anti-inflammatory activity LINS01007 compared to compound LINS01005, which may be linked to the higher affinity of the compound for H4R, suggesting the involvement of H4R in pulmonary inflammation.